2020
DOI: 10.1038/s41598-020-71569-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for circulating fibroblast growth factor 21 and 23

Abstract: Fibroblast growth factors (FGFs) 21 and 23 are recently identified hormones regulating metabolism of glucose, lipid, phosphate and vitamin D. Here we conducted a genome-wide association study (GWAS) for circulating FGF21 and FGF23 concentrations to identify their genetic determinants. We enrolled 5,000 participants from Taiwan Biobank for this GWAS. After excluding participants with diabetes mellitus and quality control, association of single nucleotide polymorphisms (SNPs) with log-transformed FGF21 and FGF23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…We are not aware of any previous GWAS for circulating FGF21 in populations of European ancestry, as done herein, but there is a GWAS for this hormone conducted in Taiwanese adults [18]. That GWAS found no genome-wide significant associations with circulating FGF21 which may be related to insufficient power due to the small sample size (n = 4201 participants).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We are not aware of any previous GWAS for circulating FGF21 in populations of European ancestry, as done herein, but there is a GWAS for this hormone conducted in Taiwanese adults [18]. That GWAS found no genome-wide significant associations with circulating FGF21 which may be related to insufficient power due to the small sample size (n = 4201 participants).…”
Section: Discussionmentioning
confidence: 81%
“…In addition to nutritional and hormonal regulation of FGF21 production [4], circulating FGF21 concentration may be genetically modified. However, a genome-wide association study (GWAS) in 4201 participants of the Taiwan Biobank identified no significant associations with circulating FGF21 [18]. Other GWAS analyses with a focus on macronutrient intake found that genetic variants in or near the FGF21 locus (rs838133 and rs838145) were associated with increased relative carbohydrate intake but decreased relative protein and fat intake [8,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previously a Genome-Wide Association Study (GWAS) reported the most important SNPs which regulate FGF21 serum levels. These SNPs were rs12565114, rs9520257 and rs67327215 ( 56 ). Investigations on the role of these SNPs and the susceptibility of people to having liver diseases may help to personalized the cure of these diseases.…”
Section: Fgf21mentioning
confidence: 99%
“…Among different members, FGF21 is a novel discovered cytokine which is significantly increased under the status of multiple lipid disorder diseases, such as dyslipidemia, obesity, and coronary artery diseases (CAD) [38]. Recently, emerging evidence demonstrated that FGF-21 plays an important role in regulating carbohydrate, lipid and phosphate metabolism, and consequently modulating the pathological progression of lipid metabolic disorder diseases [39]. Consistently, treatment with FGF-21 has been confirmed to improve the energy metabolism in hepatocytes in both rodents and non-human primates, supporting that FGF21 could be considered as a potential therapeutic method for dyslipidemia [40].…”
Section: Fibroblast Growth Factor-21 (Fgf-21)mentioning
confidence: 99%